Changes of body mass index in celiac children on a gluten-free diet - Brambilla, P.; Picca, M.; Dilillo, D.; Meneghin, F.; Cravidi, C.; Tischer, M.C.; Vivaldo, T.; Bedogni, G.; Zuccotti, G.V. (Nutrition, metabolism, and cardiovascular diseases, 2013)
Studies of adults and children with celiac disease (CD) performed mostly in tertiary care centers have reported an increased risk of overweight during gluten-free diet (GFD). We measured body mass index (BMI) of CD children followed by family pediatricians in order to estimate prevalence of underweight and overweight at diagnosis and to describe BMI changes during GFD. We compared 150 CD children (age range 2–16 yrs) under GFD from a median (IQR) time of 4.4 (4.2) years with 288 healthy children matched for gender and age. We also evaluated retrospectively BMI changes between CD diagnosis and the current evaluation. The median (IQR) BMI of CD patients was significantly lower than that of controls [−0.38 (1.46) vs. 0.09 (1.18) SDS, p < 0.0001, Italian reference data]. Using the International Obesity Task Force classifications, CD children were less frequently overweight or obese (12% vs. 23.3%, p = 0.014) and more frequently underweight (16% vs. 4.5%, p < 0.001) than controls. During GFD, there was a marked decrease of number of underweight subjects (13 vs. 27) and a minimal increase of number of overweight subjects (9 vs. 6) (p < 0.001). The frequency of overweight and obesity at diagnosis of CD and during GFD in children followed by family pediatricians is substantially lower than that reported in tertiary care centers. On the other hand, the high frequency of underweight at diagnosis confirms the need of careful personalized nutritional management.